Review: Algoritma Optimasi - Imam Yunianto; Yunus Fadhilah S (PPM Telkom University, 2023)
Abstract Optimization is needed by many people when there are two different parameters that must be achieved in conflict with each other, such as when a fisherman wants to get a large catch of fish with minimal operational costs. This is very confusing because if you want to get a lot of results, you have to spend a lot of operational costs too. However, getting large results and keeping operational costs low is a challenge for everyone. For this reason, there is a lot of research that discusses how to optimize algorithms to get the best results. This research reviews the optimization methods used to achieve that goal with different algorithms and different results. The results of this journal review are four methods in optimization research.